Pengaruh Pengetahuan Zakat dan Kemudahan Pembayaran Terhadap Keputusan Petani Membayar Zakat - Irwansyah Putra Marpaung; Marliyah, Marliyah; Rahmat Daim Harahap (Journal of Islamic Economics and Finance, 2024)
This research aims to analyze the influence of knowledge and convenience variables on farmers' decisions to pay zakat. This research is quantitative research. The population in this study was 2,185. By using random sampling techniques, a sample of 100 respondents was taken. The data processing process uses SPSS 26. The results of the research show that Knowledge has an effect of t-count t-count of 7.728 which is greater than t-table 1.648 and the significance of 0.00 is smaller than 0.05, so partially the knowledge variable has a significant effect on the decision variable ( Y). Ease of influence has a t-count of 21.886 which is greater than the t-table of 1.648 and the significance of 0.00 is smaller than 0.05, so partially the Ease variable has a significant effect on the Decision variable (Y). Simultaneously the variable knowledge (X1) and ease ( X2) together influence the farmers' decision to pay zakat as F-calculation is 325,690 > from F-table 3.864 and the significance value of F is 0.00 < 0.05, so the hypothesis can be accepted. This shows that together the independent variables consist of Knowledge (X1) and Convenience (X2) have a significant effect on the dependent variable, in this case Decision (Y).